STUDY OF INSURANCE RETURNS AS COMPARED WITH OTHER INVESTMENT OPTIONS (International Journal of Engineering Sciences & Management Research, 2018)
Insurance industry contributes to the financial sector of an economy and also provides an important social security in developing countries. The growth of the insurance sector in India has been phenomenal. The insurance industry has undergone a massive change over last few years and the metamorphosis has been noteworthy. Many insurance companies in India have managed to make their way into almost every Indian household. Government of India is also highly concern to the need of Insurance in current scenario. There are numerous private and public sector insurance companies in India that have become synonymous with the term insurance over years, offering a diversified product portfolio and excellent services to the customers. Customers are putting huge amount in the form of ULIP and Traditional products in the market through these companies to fetch Insurance cover along with returns on investment and Tax benefit.